Clear cell and endometrioid carcinomas: are their differences attributable to distinct cells of origin?. Issue 1 (7th August 2017) - Cochrane, Dawn R; Tessier‐Cloutier, Basile; Lawrence, Katherine M; Nazeran, Tayyebeh; Karnezis, Anthony N; Salamanca, Clara; Cheng, Angela S; McAlpine, Jessica N; Hoang, Lien N; Gilks, C Blake; Huntsman, David G
Abstract: Endometrial epithelium is the presumed tissue of origin for both eutopic and endometriosis‐derived clear cell and endometrioid carcinomas. We had previously hypothesized that the morphological, biological and clinical differences between these carcinomas are due to histotype‐specific mutations. Although some mutations and genomic landscape features are more likely to be found in one of these histotypes, we were not able to identify a single class of mutations that was exclusively present in one histotype and not the other. This lack of genomic differences led us to an alternative hypothesis that these cancers could arise from distinct cells of origin within endometrial tissue, and that it is the cellular context that accounts for their differences. In a proteomic screen, we identified cystathionine γ‐lyase (CTH) as a marker for clear cell carcinoma, as it is expressed at high levels in clear cell carcinomas of the ovary and endometrium. In the current study, we analysed normal Müllerian tissues, and found that CTH is expressed in ciliated cells of endometrium (both eutopic endometrium and endometriosis) and fallopian tubes. We then demonstrated that other ciliated cell markers are expressed in clear cell carcinomas, whereas endometrial secretory cell markers are expressed in endometrioid carcinomas. The same differential staining of secretory and ciliated cells was demonstrable in a three‐dimensional organoid culture system, in which stem cells were stimulated to differentiate into an admixture of secretory and ciliated cells. These data suggest that endometrioid carcinomas are derived from cells of the secretory cell lineage, whereas clear cell carcinomas are derived from, or have similarities to, cells of the ciliated cell lineage. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.